Synthesis of research issues and capacity building in water and land resources management in Ethiopia - Kamara, A. B.; McCornick, Peter G. (2003)
This paper presents an overview and synthesis of the key research and capacity building issues arising from the workshop presentations and the papers. Three days of intensive deliberations by professionals from various research, development and governmental organizations, and of diverse disciplines, backgrounds and nationalities have clearly acknowledged that water management issues remain very crucial for poverty alleviation and rural development in Ethiopia ? the overwhelming proportion of the population depends on smallholder agricultural production, which is highly constrained by water availability (absence of perennial rivers, high spatial and temporal availability of rainfall, etc.). This situation, over the years, has generated a critical need for efficient water and land management to reduce production risks and hazards, and enhance stable agricultural and livestock production. Recent decades have witnessed various efforts in the area of irrigation and supplementary irrigation (and other development initiatives), employing various water harvesting technologies, construction of micro dams, diversions structures, etc., which were largely combined with traditional yield-enhancing methods to facilitate sustainable smallholder agricultural production.